HUBUNGAN FAKTOR-FAKTOR SOSIAL EKONOMI DAN PERILAKU PENGELOLAAN SAMPAH RUMAH TANGGA DI KECAMATAN PONTIANAK TENGGARA, KOTA PONTIANAK - fahmi, muhammad fahmi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
Waste management has become one of the worst problems in urban communities such as garbage still visible and scattered everywhere. As a result of lack of community awareness in waste management various kinds of problem are detected in the environment. The purpose of this study is to determine the relationship between socio-economic conditions and people's behavior in waste management in Kecamatan Pontianak Tenggara, Kota Pontianak. This research uses a quantitative research methods, and the population consists 900 housewives in the Kecamatan Pontianak Tenggara.The sample size is calculated using the Slovin formula, and the result is 277 people. The sampling frame uses a combination of proposional sampling for area and random sampling for selecting individual sample member. Data collection techniques uses questionnaires, observations and interviews. Data analysis techniques uses the Spearman Rank Correlation statistical test. The results shows that the highest number of sample members are: graduate from Senior High School (34.7%), income larger than UMR (44.4%), housewives (71.5%), good level of knowledge (50,9%). Household habit in waste management is not supportive (51.6%). In conclusion, socio-economic conditions have low relationship with household waste management in Kecamatan Pontianak Tenggara (Correlation Coefficient 0,377** at Sig.(2-tailed) 0.0001). The community needs to raise more awareness about the problem of waste generated by each household, especially in waste management.